Governing the Digital Border: A Systematic Review of Interoperability, Accountability and Institutional Coordination in Immigration Information Systems - Muridi Makame Abdalla; Diana Rwegasira; Mahadia Tunga (Darul Yasin Al Sys, 2026)
The global transition toward e-governance has transformed immigration administration by strengthening border security, improving service efficiency, and facilitating interagency coordination. Developed economies across Europe and Asia have implemented integrated Immigration Information Systems (IIS) that combine real-time data, biometrics, and interoperable digital frameworks to manage migration securely and accountably. Nevertheless, substantial disparities persist between developed and developing countries because of limited interoperability, insufficient capacity, institutional fragmentation, and data-security concerns. This study systematically reviews peer-reviewed literature published from 2015 to 2025 to examine how interoperability, accountability, and institutional coordination can be achieved through IIS. Guided by PRISMA principles, the review synthesizes evidence from empirical studies, policy frameworks, and international case studies, focusing on technological, semantic, and organizational interoperability. It also examines accountability mechanisms related to system security, transparency, data quality, regulatory compliance, and governance arrangements spanning agencies and national borders. The findings indicate that although the literature frequently prioritizes technological interoperability, semantic alignment and strong organizational interoperability are essential for effective and sustainable system integration. Their achievement depends on clear legal mandates, robust governance structures, and effective interagency collaboration. Integrated systems in the European Union, Estonia, and Singapore demonstrate the potential of IIS to accelerate processing, strengthen security, and improve policy coherence, whereas many developing countries remain constrained by institutional, human-capacity, and infrastructural limitations. The review proposes a unified framework integrating interoperability, accountability outcomes, and institutional coordination. By synthesizing a fragmented body of scholarship and identifying critical research gaps, it provides evidence-based guidance for policymakers and system architects developing secure, accountable, and interoperable immigration information systems.